Moonpool dimensions and position optimization with genetic algorithm of a drillship in random seas - Machado, Lucas do Vale (2020)
In this work, we present a method to optimize the moonpool profile (its dimensions and position in the hull), minimizing water motion inside moonpool or motions of the ship, for a specific drillship hull in operation condition, when in head seas (β = 180.0°), for both a regular wave or a random sea. The study approach is divided in two main parts. In the first part is presented an analytical and numerical study of the water motion inside moonpool with the aim to understand the physics of the phenomenon and define the parameters for the main goal achievement. In the second part, an optimization algorithm known as Genetic Algorithm (GA) is used for the moonpool optimization. For the first part, based on previous known work in literature, an equation for the water motion inside a rectangular moonpool is deduced and from that it is possible to get important hydrodynamic coefficients as natural frequency and critical damping. From commercial CFD (Computational Fluid Dynamics) software analysis, some observation are done about the relative motion between the vessel and the water motion inside moonpool. Furthermore, it is done a study for implementation of an artificial viscous damping in a potential theory code using a lid technique. The main goal of the first part is to calculate the viscous damping in order to use in the potential theory at the second part. The optimization procedures using the in-house software created for this thesis and applies Genetic Algorithm (GA) is the main topic in second part. Results reveal the algorithm ability to find profiles that follows the optimization requirements defined by the user. Another interesting factor observed is the coupling between vessel’s heave motion and the water motion inside moonpool. Thereby, it is possible to find an optimum profile that acts as a damper of vessel motions.